Pengaruh Model Reciprocal Teaching Dipadukan dengan Think Pair Share terhadap Hasil Belajar Mikrobiologi Mahasiswa IKIP Budi Utomo - Purwaning Budi Lestari; Titik Wijayanti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2016)
Location of observation results were obtained preliminary data the value of the results obtained from the study of microbiology student class of 2012 a number of 297 students with a range (86-100) of 20% or 60 students, students with a range of values (70-85) by 23% or 68 students, while the value of students under 70 sebasar 57% or 169. The purpose of this research is as follows: Determine the influence learning model Think Pair Share Reciprocal Teaching combined with the learning outcomes of students. The study design is a quasi-experimental design (Quasi experiments). Research data analysis techniques performed by using analysis of covariance (Anacova). The results showed the average value of the lowest corrected is control by the conventional approach of 63 102 followed by 68. 923 polling stations, amounting to 71. 587 the next Reciprocal Teaching and TPS + RT amounted to 81. 644. Test homogeneity of variance between different groups or homogeneous data. An average of 4 models fell from above that showed significant are: the integration of TPS + RT RT significantly different, real different to the polling stations and significantly different to conventional (control). But for TPS and RT models are not significantly different.